An Integration of Buddhist Teachings in Stress Management - Channuwong, Sukhumpong; Ruksat, Suvin; Ploychum, Suchao (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 4 (2561): October-November 2018DO - 10.14456/jcdr-hs.2018.29, 2018)
The purposes of this research were to present an integration of Buddhist teachings in stress management, and to form a model of Buddhist teachings in stress management. The research results show that stress is one state of suffering, which is caused by an accumulation of many problems in human life. Stress occurs when a person facing some problems feels that they are beyond his or her capability to cope with. However, if a person feels that the experiencing problems are simple, and he or she is able to solve them, stress will not occur. Thus, it can be said that stress is an individual condition and is highly related to emotion, feeling and viewpoint of a person towards the problems he or she is facing. Stress may be caused by the reality of life, for examples, old age, sickness, death, and separation of loved ones, and by internal and external situations such as financial problem, work problem, family problem, economic problem, and social problem etc. Sometimes, stress may be caused by our imagination such as worry, anxiety, fear, anger, pressure, and feeling of disappointment. All kinds of stressors can cause the same sufferings because human brain cannot differentiate between real stress and imagined stress. Buddhist teachings present useful ways to cope with stress by calming the mind, controlling negative emotions and feelings through tranquility meditation, and developing wisdom and insight in order to purify the mind to be free from stress and sufferings through insight meditation. Buddhist teachings provide useful concepts and practical ways such as breathing meditation (Ãnãpãnasati) for coping with various problems that cause stress with mindfulness and consciousness. Keywords: Buddhist Teachings, Stress Management, Tranquility Meditation, Insight Meditation